THE EFFORT TO PROVIDE PROFESSIONAL NEEDS OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN THE EDUCATIONAL ENVIRONMENT - Taufiq, Muhammad; Lubis, Maesaroh (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
Education is a process to influence students to be able to adapt as well as possible to the environment so that it can cause a change in social life. While the teaching participate for directing the purpose of educational process and changes can be achieved. To create an educational atmosphere and standard qualifications, it is necessary to provide effective and efficient technology by utilizing Information and Communication Technology (ICT) based digital-devices by using computer equipment and its supporting facilities. The development of concept of education management is designed to increase the ability to manage changes and developments in education related to the achievement of purposes, policies, strategies, planning, curriculum that have been determined by the government and education authorities so that it is expected to realize the effort of professional employe that compatible with the era of development